Establishing phosphorus critical values for tomato (Solanum lycopersicum) fertilization with phosphate fertilizers on the Sudan savanna soils using three soil phosphorus extraction methods and field experimentation in Kano State, Nigeria - Yusuf, Yahaya Mohammad; Madukwe, Donald Kelechi; Kebede, Fassil (Frontiers in Agronomy, 2023)
Phosphorus (P) is an essential nutrient for tomato (Solanum lycopersicum L.) production, as it stimulates root growth by improving water use efficiency and nutrient uptake. It also helps control the metabolic processes of ATP (energy), sugars, and nucleic acids. Therefore, it is imperative to effectively manage the phosphorus requirements of tomatoes to bolster their productivity. The objective of this study was to evaluate the effectiveness of three different soil P testing methods that are suitable for the soils of Kano State, Nigeria, and to develop a critical P-value for fertilizer recommendations for tomatoes. Accordingly, sixty topsoil samples were collected for soil available P testing according to the Bray II, Mehlich 3, and Olsen methods. Moreover, to establish the phosphorus critical value (Pc) for tomatoes, a field experiment was conducted with seven different rates of P using triple super phosphate fertilizer (TSP), viz., 0, 15, 30, 45, 60, 75, and 90 kg P/ha, laid out in a randomized complete block design with three replications on 15 experimental sites representing the various agroecological zones of the state. Phosphorus fertilizer was applied and incorporated into the soil 1 week before tomato transplanting. Then, soil samples from 0 to 20 cm depth were taken 3 weeks after transplanting from all the plots across the experimental sites for separate Mehlich 3, Bray II, and Olsen extractable P analysis to determine the critical soil P (Pc) test. The study revealed that available P was varied and increased in the order of Olsen (2.19 ppm)< Mehlich 3 (5.37 ppm)< Bray II (5.44 ppm), and the Mehlich 3 and Bray II extraction methods were strongly correlated, whereas Olsen underestimated the available P, showing a weak correlation with both Mehlich 3 and Bray II. Furthermore, the study showed that phosphorus critical (Pc) values were 17.00, 14.00, and 4 ppm for Mehlich 3, Bray II, and Olsen respectively. Finally, Bray II was a more reliable method for estimating the available P on moderately acid soils as it showed the highest correlation r = 0.83 with the relative yield of the tomatoes and, therefore, was the most effective method for developing the equation for the soil test-based phosphatic fertilizer recommendation for maximizing tomato production in the soils of Kano State. Hence, the equation developed for the P fertilizer recommendation (Pr) for tomatoes in Kano State was found to be “Pr (kg P2O5 ha−1) = (14.0 − Pi) × 9.02”.